2020
DOI: 10.1021/acsnano.0c02661
|View full text |Cite
|
Sign up to set email alerts
|

Bond Dissociation and Reactivity of HF and H2O in a Nano Test Tube

Abstract: Molecular motion and bond dissociation are two of the most fundamental phenomena underpinning properties of molecular materials. We have entrapped HF and H2O molecules within the fullerene C60 cage, encapsulated within a single-walled carbon nanotube (X@C60)@SWNT where X = HF or H2O. (X@C60)@SWNT represents a class of molecular nanomaterial composed of a guest within a molecular host within a nanoscale host, enabling investigations of the interactions of isolated single di-or tri-atomic molecules with the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 61 publications
2
26
1
Order By: Relevance
“…Continuous video imaging allows for the structural analysis and monitoring of formed intermediates in real-time. Unlike in the case of frequently studied fullerenes , , or PAHs , entrapped in carbon nanotubes, our molecule is found as an isolated entity on a graphene monolayer. This circumstance prevents the oligomerization process with other fullerenes or molecules and allows us to focus solely on the intramolecular processes in granular detail.…”
contrasting
confidence: 64%
See 3 more Smart Citations
“…Continuous video imaging allows for the structural analysis and monitoring of formed intermediates in real-time. Unlike in the case of frequently studied fullerenes , , or PAHs , entrapped in carbon nanotubes, our molecule is found as an isolated entity on a graphene monolayer. This circumstance prevents the oligomerization process with other fullerenes or molecules and allows us to focus solely on the intramolecular processes in granular detail.…”
contrasting
confidence: 64%
“…At this point, it should be mentioned that , unlike in the depiction in Figure a, the vast majority of electrons is scattered at an angle below 5°, as indicated in Figure b by the differential elastic-scattering cross-section for hydrogen at 80 keV kinetic energy. Recently, Biskupek et al demonstrated that the absorbed energy E T of an atom 1 can be further passed to a second atom 2 to give , which follows the relationship expressed in eq 2 in Figure a . The relationship between the e-beam energy uptake of carbon and hydrogen atoms and the transfer to a second atom as a function of acceleration voltage is shown in Figure b.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…16 The G-values are dependent on the energy of the initial fast electron and the chemistry of the liquid sample and often quoted as the number of molecular yield per 100 eV absorbed energy. [20][21] For instance, the G-values of water radiolysis for 300 keV electron beam obtained by Hill and Smith are: 22 that the direct knock-on collisions caused by the electron beam are the main driving force for dissociating water molecules in a specific case of molecular confinement in a sub-nanometre space. They also addressed that the dissociation processes caused by electron-electron interactions such as radiolysis are quickly reversed due to the confined space.…”
mentioning
confidence: 99%